Dalla tonaca alla toga: il monaco greco-ortodosso Ireneo capofila di un cambiamento? (Stato, Chiese e pluralismo confessionale, 2019)
SOMMARIO: 1. Premessa in fatto - 2. L’impugnazione al Consiglio di Stato greco - 3. La recente sentenza (7 maggio 2019, C 431-17) della Corte di Giustizia UE e il suo approdo ermeneutico.From the cassock to the court dress: is Ireneo, the Greek orthodox monk, leader of a change?ABSTRACT: The European Court of Justice, declares the Greek legislation contrary to the UE law, according to the judgment of 7 May 2019, C-431/17. The Greek legislation prohibits a monk qualified for the legal profession in Cyprus from enrolling in the register and practicing the profession, in the host Member State, using the title of the Member State of origin.